The Effectiveness of Internal Control According to International Auditing Standards and Its Role in Achieving Sustainable Development (Field Study on Jordanian Government Institutions) - Alkhalidy, Faris Abdulzahra Abdulhussin; Alwan, Bader Mohammed; Alzbady, Balassem Mohammed Ibraheem (South Asian Journal of Social Sciences and Humanities, 2025)
This study aims to propose the preparation of an internal control system for government institutions according to international standards and to show the possibility of applying the internal control system according to international standards in government institutions The number of the sample to which the questionnaire was distributed was (30 individuals) of employees and managers in government institutions and sectors. The general indicator issued by the United Nations contains seventeen indicators that measure sustainable development, and the report on the effective internal control system should include related activities. With sustainable development, which necessarily affects it, and the effective internal control system represents the internal activity in government institutions that is concerned with monitoring indicators related to sustainable development. The researcher also recommends that government institutions should be interested in sustainable development as they are the bodies responsible for the mechanisms for achieving it, and this imposes on government institutions to maintain this degree and work to improve it.
Keywords: Internal control system; internal control standards; sustainable development; sustainable development index